1 Medical examiners and attending practitioners collaborate to improve overall End-of-Life Care and support for bereaved persons: A snapshot of the Margaret Centre experience. (14th March 2023) - Abarshi, Ebun; Manoharan, Bairavi; Bourke, Sean; Goodward, Sally; Watson, Alan
Abstract : Background: In 2021/22, 1 in 4 of all Whipps Cross hospital deaths occurred on the Margaret Centre (MC), an 11-bedded specialist palliative care unit in London. The centre provides specialist services to Waltham Forest and its environs, through healthy collaborations at various levels. Medical examiners (MEs) routinely support qualifying attending practitioners (QAPs), to improve the quality and accuracy of the medical cause of death certification. In addition, MEs engage with the bereaved, to ensure greater safeguards for the public. Aim: To showcase ME-QAP relationship on a specialist palliative care inpatient unit. Method: Mixed-method approach, comprising retrospective extrapolation of all deaths from 1 st April to 31 st May 2022, and qualitative analysis of relevant data (convenience sampling). Results: 2021/22 ME vs. QAP cohort: Total expected deaths = 54; scrutinised by MEs (85%). All deaths on MC: Age: 43–100y Males 22 (41%) Length of stay on MEs: 0–22days Reason for admission: End-of-life Care 43 Symptom control 10 Outlier 1 Scrutinised in retrospect and real-time (46) Monday – 22%; Tuesday – 46%; Wednesday – 9%; Thursday – 17%; Friday – 6% Not-scrutinised (8): Weekend (62%) [Other reasons: Outlier (25%); Family pressures (25%); Direct coronial referral (12%)] Coronial decisions (6) Port-mortem (50%), Advice (33%), Inquest (17%) MC QAP response to scrutiny of 'expected deaths' 'Is it necessary' 'Sometimes laborious' 'A valuable process' – after witnessing the first successful body donation to LAO 'On-call service is desirable' Conclusion: Pre-emptive and preparatory scrutiny of deaths is valued by all, and appears to have reduced complaints somewhat. Research is required to evaluate Trust-wide acceptability of the practice.